Revisiting the determinants of consumption: A bayesian model averaging approach - DENİZ, PINAR (My University, 2023)
This study revisits the widely researched area of the consumption function using Bayesian Model Averaging (BMA) for a panel of EU countries to deal with the uncertainty of potential determinants, using the convergence club analysis to construct homogeneous groups by income. BMA suggests that income is the only variable that is found to be a strong determinant across different country groups, whereas other variables have varying importance for different country groups
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Social Sciences and Humanities; Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Ekonomi, Ekonometri ve Finans (çeşitli); Genel Ekonomi, Ekonometri ve Finans; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Economics, Econometrics and Finance (miscellaneous); General Economics, Econometrics and Finance; Social Sciences & Humanities; consumption function; bayesian model averaging